The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update - Ramli Hasan Aif; Soeparto Soeparto (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update